2015
DOI: 10.1186/s12936-015-0854-5
|View full text |Cite
|
Sign up to set email alerts
|

Ethical considerations in malaria research proposal review: empirical evidence from 114 proposals submitted to an Ethics Committee in Thailand

Abstract: BackgroundMalaria research is typically conducted in developing countries in areas of endemic disease. This raises specific ethical issues, including those related to local cultural concepts of health and disease, the educational background of study subjects, and principles of justice at the community and country level. Research Ethics Committees (RECs) are responsible for regulating the ethical conduct of research, but questions have been raised whether RECs facilitate or impede research, and about the qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Most studies reported that ethical issues were especially common in clinical trials, including in the ethical review process, standard of care, incentives and reimbursement, and insurance and indemnity [ 17 20 ]. A previous study stratified the ethical issues raised in a broad spectrum of research proposals submitted to the Faculty of Tropical Medicine Ethics Committee (FTM-EC) at Mahidol University [ 20 ]. The findings of the study described ethical considerations in the review process, but did not focus on ICP issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies reported that ethical issues were especially common in clinical trials, including in the ethical review process, standard of care, incentives and reimbursement, and insurance and indemnity [ 17 20 ]. A previous study stratified the ethical issues raised in a broad spectrum of research proposals submitted to the Faculty of Tropical Medicine Ethics Committee (FTM-EC) at Mahidol University [ 20 ]. The findings of the study described ethical considerations in the review process, but did not focus on ICP issues.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the study described ethical considerations in the review process, but did not focus on ICP issues. The ICP is particularly critical in studies that use new or linked specimens or data in human research subjects, and deficits in the ICP are often identified in a REC review [ 20 22 ]. This study focused particularly on ICP in malaria research, since (a) about one-third of proposals submitted to FTM-EC were related to malaria and FTM has been one of the institutes contributing significantly to global research publication on malaria, and (b) ICP in malaria research is crucial as malaria studies are generally conducted among the vulnerable, including children, ethnic groups, refugee and cross-border populations, who are mostly illiterate and reside in remote, limited healthcare-access and/or low-resource settings.…”
Section: Introductionmentioning
confidence: 99%